A framework for supporting intelligent and flexible workflow-based engineering design process. (11th October 2007) - Wang, Dongbo; Yan, Xiu-Tian; Ion, William J.; Wang, Runxiao
To support an efficient management of a creative and dynamic Engineering Design Process (EDP), this paper proposes a new intelligent and flexible workflow-based EDP management framework entitled EnDesProM. The Autonomic Object (AO) based on autonomic computing is embedded in the nodes of flexible workflow to ensure the intelligence of the framework. An innovative flexible workflow modelling method based on dynamic instance creation is proposed as part of the EnDesProM. Both the formalised definition and graphical expression of the EDP models are introduced to ensure the rigour of the approach. The architecture of the intelligent workflow is designed and the application of the weighted Certainty Factor (CF) model in the knowledge expression is investigated to deal with the incomplete information in EDP. The EnDesProM has been evaluated through an EDP in a Make-to-Order (MTO) company and the results show that EnDesProM can support the creative and dynamic EDP satisfactorily, though further improvements are required.